2012
DOI: 10.1002/jwmg.379
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for estimating raccoon abundance: Implications for disease vaccination programs

Abstract: Accurate estimates of demographic parameters are critical to the management of wildlife populations, including management programs focused on controlling the spread of zoonotic diseases. Rabies managers in the United States Department of Agriculture (USDA) have applied a simple raccoon (Procyon lotor) abundance index (RAI) based on cumulative catch of unique raccoons per unit area to determine vaccine‐bait distribution densities. This approach was designed to allow for both the collection of biological samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Fruits such as, mango, jackfruit, guava, black berry, and litchi were mostly damaged during the fruiting season, whereas other types of fruit (e.g., banana, papaya, sapodilla, hog plum, and immature coconut) were damaged throughout the year. This suggests that the crop-raiding patterns by langurs in Keshabpur might be determined by seasonal aspects of the available human-edible fruits, rather than by the scarcity of foods, as observed in several previous studies (e.g., (Beasley & Rhodes, 2008;Chiyo, Cochrane, Naughton, & Basuta, 2005;Sukumar, 1989).…”
Section: Seasonal Aspect Of Crop Damagesupporting
confidence: 57%
“…Fruits such as, mango, jackfruit, guava, black berry, and litchi were mostly damaged during the fruiting season, whereas other types of fruit (e.g., banana, papaya, sapodilla, hog plum, and immature coconut) were damaged throughout the year. This suggests that the crop-raiding patterns by langurs in Keshabpur might be determined by seasonal aspects of the available human-edible fruits, rather than by the scarcity of foods, as observed in several previous studies (e.g., (Beasley & Rhodes, 2008;Chiyo, Cochrane, Naughton, & Basuta, 2005;Sukumar, 1989).…”
Section: Seasonal Aspect Of Crop Damagesupporting
confidence: 57%
“…The disparity between RDIs and Huggins estimates generally increased at higher raccoon abundance. In a comparison study exploring calibration of RDIs, Beasley et al (2012) reported that on average RDIs used by Wildlife Services were 48% lower than mark‐recapture estimates in fragmented agricultural areas in north‐central Indiana, USA. However, from a rabies management perspective, 20 of our 26 density groups aligned with bait densities suggested by both mark‐recapture estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It is large, mature trees, as a critical habitat attribute, that provide raccoons with sufficiently large tree cavities for reproduction and denning (Chamberlain et al 2002, Henner et al 2004. Abundance of female raccoons was positively related to den tree density in the agricultural landscape of north central Indiana, USA (Beasley et al 2012). Raccoons are the effective predators of avian nests and small mammals, and also scavenge for food from human residence in the rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to expect raccoon populations increase in the landscape disturbed by human residential establishment and agriculture owing to enhanced food availability (Beasley et al 2011, Troyer et al 2014b. With increasing raccoon population size and limited number of mature trees for maternal denning, raccoon populations may become density dependently regulated and become stabilized at the carrying capacity (Beasley et al 2012). Raccoon populations reached an equilibrium with the finite rate of increase being stabilized at 1.0 in a protected area in Florida, USA (Troyer et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation